Equatorial ionospheric response to storm-time electric fields during two intense geomagnetic storms over the Brazilian region using a Disturbance Ionosphere indeX. (15th October 2021) - Picanço, G.A.S.; Denardini, C.M.; Nogueira, P.A.B.; Barbosa-Neto, P.F.; Resende, L.C.A.; Chen, S.S.; Carmo, C.S.; Moro, J.; Romero-Hernandez, E.; Silva, R.P.
Abstract: In this work, we use a new version of the Disturbance Ionosphere Index (DIX) to evaluate ionospheric disturbances over the Brazilian region during two intense geomagnetic storms (22 June 2015 and St. Patrick's Day storm). The DIX values were obtained from the deviation of Total Electron Content (TEC) data acquired during the geomagnetically disturbed days in relation to a non-perturbed TEC reference to provide a single and dimensionless value of the ionospheric degree of perturbation during the magnetic events. Moreover, we used F-layer parameters ( foF2 and h'F ) measured by ionosondes to identify the ionospheric impacts of storm-time electric fields observed as perturbations in the DIX. Our results show that the geomagnetic storms caused large perturbations in the ionosphere as observed by increases/decreases in the TEC over different latitudinal sectors, which were also observed in the foF2, h'F, and DIX values. Therefore, the DIX has shown to be a useful parameter for observing the ionospheric impact under prompt penetration and disturbance dynamo electric field events, as well as to ionospheric disturbances related to the pre-storm period. Finally, from those observations, we found that the DIX resembles the ionosonde measurements, and that it is consistent with the physical processes that occurred during each phase of the geomagnetic storms. Highlights: Pre-storm ionospheric effects were observed in the DIX over equatorial and low latitudes. Ionospheric responses related to the disturbance dynamo were observed in the DIX. Prompt Penetration Electric Fields caused the higher DIX perturbations with a scale level of 5.